Formulation of Seaweed (Eucheuma cottonii Doty) Lotion - Hamsinah, Hamsinah; Suhaenah, Asriani; Mulyana, Imam Dwiyan (Pharmaceutical Reports, 2023)
Seaweed (Eucheuma cottonii Doty) has potential as an antioxidant because it contains kappa-carrageenan which can counteract free radicals. Formulation of seaweed (Eucheuma cottonii Doty) into lotion preparations can minimize the negative effects of sun exposure, because it can reflect solar radiation or work as a physical sunscreen. To give the maximum effect, particle size reduction is carried out, so that the smaller the particle size of the seaweed powder, the surface area increases. This study aims to determine the formulation and evaluate the preparation of lotion from seaweed powder. This research was conducted using an experimental method. The lotion was made with three variations of seaweed powder concentration (Eucheuma cottonii Doty), namely 2.5%, 3% and 5%. Tests were carried out before and after accelerated conditions at 5oC and 35oC for 12 hours each for 12 cycles with test parameters including organoleptic, homogeneity, pH, spreadability, viscosity and flow type. The results obtained in the organoleptic test showed no change in the three formulas both before and after the accelerated condition. The pH test showed that Formula 2 and Formula 3 still showed that the preparation remained in the skin pH range for sunscreen. In the homogeneity test, all preparations were homogeneous, as well as the spreadability test met the test requirements criteria. Based on the tests carried out, it can be concluded that formulas 2 and 3 have optimum stability.